Indonesia Foreign Trade Policy in Protecting Domestic Textile Industry Products from the Influx of Illegal Textile Import - Sood, Muhammad; Valencia Husni; Sri Maryati; Lale Puspita Kembang (Faculty of Law, University of Mataram, 2025)
This study aims to analyze international trade regulations related to the importation of goods into Indonesia; examine the implications of the widespread circulation of illegal textile products on the domestic textile industry; and assess Indonesia import policies in providing protection for domestic textile production. This research employs a normative legal method, utilizing both the Statutory Approach and the Conceptual Approach. Legal materials were collected through a literature review, using documentation techniques to analyze various sources of law in the form of statutory regulations. The results of the study indicate that international trade regulations are established in various laws, including Law Number 17 of 2006 concerning Customs; Law Number 7 of 2014 concerning Trade; Law Number 7 of 1996 concerning Food; and Law Number 8 of 1999 concerning Consumer Protection. The widespread circulation of illegal textile products (commonly known as thrifting) has led to several negative impacts, including the closure of numerous domestic textile industries, increased unemployment, and reduced state revenue. To address these issues, the Indonesian government has implemented various policies to protect the domestic textile industry through both preventive and repressive legal measures. Preventive legal protection includes regulations on import policy and supervision, guidance for business actors (producers, importers, and distributors), and public outreach to consumers. Repressive legal protection involves the imposition of administrative, civil, and criminal sanctions on those engaged in the illegal importation of textile products.